Hematologic complications in vascular malformations: A case study of 2 patients - Matus, Iwona; Bator, Kaja; Machaj, Weronika; Krzemienowska-Cebulla, Aleksandra; Dorochowicz, Mateusz; Senat, Hanna; Korbecki, Adrian; Szuba, Andrzej; Rabczyński, Maciej (Journal of Education, Health and Sport, 2024)
Vascular malformations are congenital vascular anomalies resulting from a disruption in the vasculogenesis process. (1) They are congenital changes that enlarge as the child develops and do not undergo spontaneous involution. They can be classified based on the type of vessels involved (capillary, arterial, venous, lymphatic, mixed) and the nature of the vascular flow (low-flow and high-flow). The clinical presentation of vascular malformations is highly diverse, and despite being congenital, they can remain asymptomatic for a long time, complicating the diagnostic process. (1,3) The presence of malformations carries the risk of health-threatening complications. One such complication is Kasabach-Merritt syndrome, characterized by thrombocytopenia, microangiopathic hemolytic anemia, and consumptive coagulopathy in the presence of a rapidly enlarging vascular tumor. (4,5) Another threat is a coagulopathy limited to the vascular anomaly (LIC). It is characterized by elevated D-dimers and fibrin degradation products, low levels of fibrinogen, FV, FVIII, FXIII, and antithrombin, and sometimes mild to moderate thrombocytopenia. (6,7) Early implementation of anticoagulant therapy allows for the avoidance of health-threatening conditions and the development of disseminated intravascular coagulation syndrome (DIC). (8)